2018
DOI: 10.15625/2525-2518/56/2a/12690
|View full text |Cite
|
Sign up to set email alerts
|

Removal of O,m,p-Xylene From Air Samples on Oxidized Carbon Nanotubes Cartridges

Abstract: Carbon nanotubes (CNTs) have been considered as an excellent adsorbent in environmental engineering, especially for treatment of volatile organic compounds (VOCs). The paper presents a new approach for the selective adsorption of Xylene isomers from air samples using nanomaterial based on oxidized multiwalled carbon nanotubes. In the first study, the functionalization of two oxidized MWCNTs was achieved with hydrogen peroxide and sodium hypochlorite. The characterization of functionalized CNTs (CNT-NaOCl, CNT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…This study showed that the efficiency of nanoadsorbents was significant in removing xylene from the air [5]. In another study, the removal of Ortho, Meta, and para-xylene from the air samples was carried out on an oxidized carbon nanotube cartridge as an adsorbent by Le Huu Quynh Anh et al In this study, the oxidized carbon nanotube with carbonyl groups significantly increased the adsorption capacity of xylene isomers [6]. In another study by Lu et al, the multi-walled carbon nanotubes were oxidized with sodium hypochlorite and used to remove ethyl benzene and para-xylene from aqueous solutions and significantly improved the removal of benzene and para-xylene [7].…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…This study showed that the efficiency of nanoadsorbents was significant in removing xylene from the air [5]. In another study, the removal of Ortho, Meta, and para-xylene from the air samples was carried out on an oxidized carbon nanotube cartridge as an adsorbent by Le Huu Quynh Anh et al In this study, the oxidized carbon nanotube with carbonyl groups significantly increased the adsorption capacity of xylene isomers [6]. In another study by Lu et al, the multi-walled carbon nanotubes were oxidized with sodium hypochlorite and used to remove ethyl benzene and para-xylene from aqueous solutions and significantly improved the removal of benzene and para-xylene [7].…”
Section: Introductionmentioning
confidence: 82%
“…The adsorption of BTEX on carbon nanotube cartridges from air samples was reported by Le et al and the results showed that the CNTs had high potential for BTEX adsorption due to their microporous structure and high surface area [9]. They showed that the oxidized CNTs with carbonyl groups increased its adsorption capacity for these isomers [6]. Also, Shahi Ahangar showed that the photocatalytic removal efficiency in the concentrations of 50, 100, and 300 ppm was equal to 87.8%, 98.9%, and 90.8%, respectively [10].…”
Section: Introductionmentioning
confidence: 85%